Pengaruh Good Corporate Governance dan Nilai Perusahaan Terhadap Tax Advoidance - Haryadi; Erzia Yetri; Ilham Wahyudi (Magister Ilmu Akuntansi Universitas Jambi, 2020)
This study aims to determine the effect of Good Corporate Governance which is proxied by variabel managerial ownership, independent directors, the committee audit,and firm value of the Tax Avoidance at the companies listed in the Indoensia Stock Exchange Period 2013-2017. The population in this study is all the company in BEI. The sampling techique using purposive sampling. The data analysis technique used is by using multiple regression. Statistial hypothesistesting using test t. The results showes that: (1)Managerial ownership not effect on taxavidance, (2) independent directors not effect on tax avoidance, (2) committe audit effect on tax avoidance, (4)firm value not effect on tax avoidance. Keywords: Good Corporate Governance, Tax Avoidance , Managerial Ownership, Independent Directors, The Committee Audit, Firm Value.